Transcriptome profiles evaluation of Leishmania braziliensis promastigotes subjected to temperature shifts in vitro (2019)
The increasing of the temperature is one of the principal consequences of the climate change, which affect human populations due of the emergence and re-emergency of infection diseases. The Leishmaniases are diseases cause by protozoans’ parasites of the genus Leishmania; these diseases are composed by different clinical manifestations, one of the most important in the New World is Cutaneous Leishmaniasis for which the most common causative species is Leishmania braziliensis. This species as the other members of the Trypanosomatidae family present a genomic plasticity and a particular gene expression regulation that allow to the parasites to adapt and response to several stimulus, for that reason the aim of this study is evaluate the transcriptome profiles of L. braziliensis promastigotes subjected to temperature shifts. To reach this aim the authors performed an RNA-Seq that permitted to find several genes associated with a direct response to the treatments; also, through the growth curves done the authors evidenced a decrease in the cell proliferation in all the temperatures tested, where the most affected was 30°C. The results obtained in this study demonstrated a fast response of L. braziliensis promastigotes to temperature shifts.